A study of attitudes, beliefs and organisational barriers related to safe emergency oxygen therapy for patients with COPD (chronic obstructive pulmonary disease) in clinical practice and research. Issue 1 (5th May 2016) - O'Driscoll, B Ronan; Bakerly, Nawar Diar; Caress, Ann-Louise; Roberts, June; Gaston, Miriam; Newton, Mark; Yorke, Janelle
Abstract : Background: Patients can be harmed by receiving too little or too much oxygen. There is ongoing disagreement about the use of oxygen in medical emergencies. Methods: This was a mixed methods study (survey, telephone interviews and focus groups) involving patients, the public and healthcare professionals (HCPs). Results: 62 patients with chronic obstructive pulmonary disease (COPD), 65 members of the public, 68 ambulance crew members, 22 doctors, 22 nurses and 10 hospital managers took part. For five factual questions about oxygen therapy, the average score for correct answers was 28% for patients with COPD, 33% for the general public and 75% for HCPs. The HCPs had an average score of 66% for five technical questions. Patients (79%) and members of the public (68%) were more likely than HCPs (36%) to believe that oxygen was beneficial in most medical emergencies and less likely to have concerns that it might harm some people (35%, 25% and 68%). All groups had complex attitudes about research into oxygen use in medical emergencies. Many participants would not wish for themselves or their loved ones to have their oxygen therapy determined by a randomised protocol, especially if informed consent was not possible in an emergency situation. Conclusions: We have found low levels of factual knowledge about oxygen use among patients with COPD and the general public and many false beliefs about the potential benefits and harms of using oxygen. HCPs had a higher level of factual knowledge. All groups had complex attitudes towards research into emergency oxygen use.